Emotional intelligence in Belva Plain’s Blessings - Nori Indriyani; Rahmi Munfangati (Universitas Islam Sultan Agung, 2019)
Everyone faces emotional challenges. It can influence their behavior since emotion is an incredibly strong drive on human behavior. This powerful emotion can lead someone to take actions that he might not regularly do, or keep away from the conditions that someone enjoys. Emotionality is related to a range of psychological phenomena, including mood, temperament, personality, and motivation. The ability to control emotions in the self and others is called Emotional Intelligence (EI). EI can be found not only in real life but in literary works such as a novel. In line with that interesting topic, this article, therefore, explores the EI and the implications of EI of the main character in Belva Plain’s Blessings. In analyzing the novel, the study applied a psychological approach. The technique of analyzing the data was a qualitative descriptive method. The findings of the study showed Jennie’s EI, that is composed of emotional self-awareness, self-regulation, motivation, and social skills. Furthermore, the results revealed the implications of Jennie’s EI; she becomes successful because she is good at self-regulation and motivation. She is also good at self-awareness, empathy and social skills, so she has better interpersonal relations.